The FREQUENCY OF STRESS HYPERGLYCEMIA AND MORTALITY IN PATIENTS WITH HYPERGLYCEMIA IN MEDICAL INTENSIVE CARE UNIT - Satti, Shahzeb Ahmed; Khattak, Abdul Latif; Tariq, Abdul Moueed; Majoka, Sultan Mehmood; Naeem, Arshad; Din, Rafi Ud (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess the frequency of stress hyperglycemia and mortality in patients with hyperglycemia admitted in medical Intensive Care Unit.Study Design: Cross-sectional study.Place and Duration of Study: Medical Intensive Care Unit, Combined Military Hospital Quetta, from Nov 2018 to Jun 2019.Methodology: A total of 150 adult patients of age between 18-80 years, of both genders, with Intensive Care Unit stay >24 hours, who were treated in medical Intensive Care Unit during study period, were included in the study. Those patients with duration of stay